Black Like Me - Griffin, John Howard; Bonazzi, Robert (New York, NY Signet, 1996)
The Deep South of the late 1950's was another country: a land of lynchings, segregated lunch counters, whites-only restrooms, and a color line etched in blood across Louisiana, Mississippi, Alabama, and Georgia. White journalist John Howard Griffin, working for the black-owned magazine Sepia, decided to cross that line. Using medication that darkened his skin to deep brown, he exchanged his privileged life as a southern white man for the disenfranchised world of an unemployed black man. What happened to John Howard Griffin--from the outside and within himself--as he made his way through the segregated Deep South is recorded in this searing work of nonfiction. Educated and soft-spoken, John Howard Griffin changed only the color of his skin. It was enough to make him hated ... enough to nearly get him killed. His audacious, still chillingly relevant eyewitness history is a work about race and humanity every American should read.
Originally published: Boston : Houghton Mifflin, 1961.
74965
Keywords: Griffin, John Howard, -- 1920-1980; African Americans -- Southern States; Southern States -- Race relations; Texas -- Biography